Study on Surface Heat Budget of Various Pavements for Urban Heat Island Mitigation - Hideki Takebayashi; Masakazu Moriyama (Advances in Materials Science and Engineering)
The surface heat budgets of various pavement surfaces are studied with the aim of mitigating the urban heat island effect. In this study, the thermal characteristics of pavements are examined using data from observations. The net radiation, surface temperature, temperature under the surface, conduction heat flux, and core weight for each experimental surface are recorded, together with the weather conditions at the time of observation. The latent heat flux is estimated from the observed weight of the cores. The surface heat budget under the same weather conditions is examined, and the sensible heat flux from each target surface is calculated. The parameters that influence the surface heat budget, for example, solar reflectance (albedo), evaporative efficiency, heat conductivity, and heat capacity, are examined. On a typical summer day, the maximum reduction in the sensible heat flux from that on a normal asphalt surface is about 150 W/m2 for an asphalt surface with water-retaining material and about 100 W/m2 for a cement concrete surface with water-retaining material, depending on the albedo of each surface.